Voluntary exercise induces anxiety-like behavior in adult C57BL/6J mice correlating with hippocampal neurogenesis - Fuß, Johannes; Ben Abdallah, Nada M.-B.; Vogt, Miriam A.; Touma, Chadi; Pacifici, Pier Giorgio; Palme, Rupert; Witzemann, Veit; Hellweg, Rainer; Gass, Peter (Hippocampus, 2010)
Several studies investigated the effect of physical exercise on emotional behaviors in rodents; resulting findings however remain controversial. Despite the accepted notion that voluntary exercise alters behavior in the same manners as antidepressant drugs, several studies reported opposite or no effects at all. In an attempt to evaluate the effect of physical exercise on emotional behaviors and brain plasticity, we individually housed C57BL/6J male mice in cages equipped with a running wheel. Three weeks after continuous voluntary running we assessed their anxiety- and depression-like behaviors. Tests included openfield, dark-light-box, elevated O-maze, learned helplessness, and forced swim test. We measured corticosterone metabolite levels in feces collected over a 24-h period and brain-derived neurotrophic factor (BDNF) in several brain regions. Furthermore, cell proliferation and adult hippocampal neurogenesis were assessed using Ki67 and Doublecortin. Voluntary wheel running induced increased anxiety in the openfield, elevated O-maze, and dark-light-box and higher levels of excreted corticosterone metabolites. We did not observe any antidepressant effect of running despite a significant increase of hippocampal neurogenesis and BDNF. These data are thus far the first to indicate that the effect of physical exercise in mice may be ambiguous. On one hand, the running-induced increase of neurogenesis and BDNF seems to be irrelevant in tests for depression-like behavior, at least in the present model where running activity exceeded previous reports. On the other hand, exercising mice display a more anxious phenotype and are exposed to higher levels of stress hormones such as corticosterone. Intriguingly, numbers of differentiating neurons correlate significantly with anxiety parameters in the openfield and dark-light-box. We therefore conclude that adult hippocampal neurogenesis is a crucial player in the genesis of anxiety. © 2009 Wiley-Liss, Inc.